Financing for equity for women's, children's and adolescents' health in low- and middle-income countries: A scoping review. - Lama Bou-Karroum; Domenico G Iaia; Fadi El-Jardali; Clara Abou Samra; Sabine Salameh; Zeina Sleem; Reem Masri; Aya Harb; Nour Hemadi; Nadeen Hilal; Layal Hneiny; Sahar Nassour; et al. (Public Library of Science (PLoS), 2024)
Over the past few decades, the world has witnessed considerable progress in women's, children's and adolescents' health (WCAH) and the Sustainable Development Goals (SDGs). Yet deep inequities remain between and within countries. This scoping review aims to map financing interventions and measures to improve equity in WCAH in low- and middle-income countries (LMICs). This scoping review was conducted following Joanna Briggs Institute (JBI) guidance for conducting such reviews as well as the PRISMA Extension for Scoping Reviews (PRISMA-ScR) for reporting scoping reviews. We searched Medline, PubMed, EMBASE and the World Health Organization's (WHO) Global Index Medicus, and relevant websites. The selection process was conducted in duplicate and independently. Out of 26 355 citations identified from electronic databases, relevant website searches and stakeholders' consultations, 413 studies were included in the final review. Conditional cash transfers (CCTs) (22.3%), health insurance (21.4%), user fee exemptions (18.1%) and vouchers (16.9%) were the most reported financial interventions and measures. The majority were targeted at women (57%) and children (21%) with others targeting adolescents (2.7%) and newborns (0.7%). The findings highlighted that CCTs, voucher programs and various insurance schemes can improve the utilization of maternal and child health services for the poor and the disadvantaged, and improve mortality and morbidity rates. However, multiple implementation challenges impact the effectiveness of these programmes. Some studies suggested that financial interventions alone would not be sufficient to achieve equity in health coverage among those of a lower income and those residing in remote regions. This review provides evidence on financing interventions to address the health needs of the most vulnerable communities. It can be used to inform the design of equitable health financing policies and health system reform efforts that are essential to moving towards universal health coverage (UHC). By also unveiling the knowledge gaps, it can be used to inform future research on financing interventions and measures to improve equity when addressing WCAH in LMICs.